Quantum dot particle assembly and preparation method thereof, photoconversion device preparation method, quantum dot particle
By using the preparation method of quantum dot particle aggregates in the preparation of quantum dot diffusion plates, the combination of polymer particles and quantum dots is used to solve the problem of quantum dot damage caused by high-temperature granulation, and the light output efficiency and lifetime of the photoconverter device are improved.
Patent Information
- Application Number
- CN202110650160.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-02
- Filing Date
- 2021-06-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-06-10
AI Technical Summary
Existing quantum dot diffusion plates are easily damaged in high-temperature granulation processes, resulting in low light output efficiency and short life.
Using a preparation method of a quantum dot particle aggregate, the photoconversion device is prepared by mixing and drying the first polymer particles, the first quantum dot solution and the second polymer solution to form a aggregate containing a plurality of quantum dot particles, and melt extrusion and solidification are carried out through a crushing treatment or a non-crumbing treatment to prepare a photoconversion device.
It effectively avoids damage to quantum dots by high-temperature processes, improves the performance of quantum dot particles and aggregates, and extends the light output and life performance of the photoconverting device.
Smart Images

Figure CN114989458B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of quantum dot applications, and more specifically, to a quantum dot particle assembly and a preparation method thereof, a preparation method of a photoconversion device, and quantum dot particles. Background Art
[0002] Quantum dot light conversion devices are used in backlight components in the display field to improve the color expression of display devices. The current mainstream product form is quantum dot diaphragms, which include two barrier films and a quantum dot layer. However, quantum dot diaphragms still face the problem of high costs. Recently, quantum dot diffuser plates have been proposed to combine the functions of quantum dots and diffuser plates. In the processing of quantum dot diffuser plates, quantum dots and white materials must first be granulated. The high temperature (200°C+) required for the granulation process can easily damage quantum dots, resulting in low light output efficiency and low lifespan of quantum dot diffuser plates. Summary of the invention
[0003] The purpose of the present application is to provide a quantum dot particle aggregate and a preparation method thereof, a preparation method of a photoconversion device and quantum dot particles, so as to improve the performance of the quantum dot particles and the aggregate, and further improve the light output and life performance of the photoconversion device.
[0004] According to the first aspect of the present application, a method for preparing a quantum dot particle aggregate is provided, wherein a plurality of first polymer particles, a first quantum dot solution and a second polymer solution are mixed and dried to obtain an aggregate containing a plurality of quantum dot particles A, wherein the quantum dot particle A comprises a core of a first polymer particle and a second polymer shell formed by a second polymer, wherein a plurality of first quantum dots are located in the second polymer shell, and the minimum size of the first polymer particle is greater than or equal to 0.3 mm.
[0005] Furthermore, the aggregate containing multiple quantum dot particles A is crushed to obtain multiple quantum dot particles A, and the multiple quantum dot particles A and a third polymer solution are mixed and dried to obtain an aggregate containing multiple quantum dot particles B, wherein the quantum dot particle B includes a core of the quantum dot particle A and a shell of a third polymer formed by the third polymer.
[0006] Furthermore, the aggregate containing multiple quantum dot particles A is crushed to obtain multiple quantum dot particles A, and the multiple quantum dot particles A are mixed with the second quantum dot solution and the third polymer solution and dried to obtain an aggregate containing multiple quantum dot particles B', wherein the quantum dot particle B' includes a core of the quantum dot particle A and a shell of a third polymer formed by the third polymer, and multiple second quantum dots are located in the shell of the third polymer.
[0007] Furthermore, the aggregate containing multiple quantum dot particles B is crushed to obtain multiple quantum dot particles B, and the multiple quantum dot particles B, the second quantum dot solution and the fourth polymer solution are mixed and dried to obtain an aggregate containing multiple quantum dot particles C, wherein the quantum dot particle C includes a core of the quantum dot particle B and a shell of a fourth polymer formed by the fourth polymer, and multiple second quantum dots are located in the shell of the fourth polymer.
[0008] Further, the fourth polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer and polyethylene terephthalate.
[0009] Furthermore, the second quantum dot solution includes 0.1 wt% to 5 wt% of the second quantum dots, and the second quantum dots are the same as or different from the first quantum dots.
[0010] Furthermore, the mass ratio of the plurality of first polymer particles to the second polymer is 100:1 to 100:10, and the mass ratio of the first quantum dots to the second polymer is 0.1:100 to 5:100.
[0011] Furthermore, the first quantum dot solution comprises 0.1 wt% to 5 wt% of the first quantum dots.
[0012] Furthermore, the first polymer particles are in the shape of a cylinder or a cuboid.
[0013] Furthermore, the material of the first polymer particles includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer and polyethylene terephthalate.
[0014] Furthermore, the second polymer or the third polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer and polyethylene terephthalate.
[0015] According to the second aspect of the present application, a method for preparing a photoconversion device is provided, and the above-mentioned quantum dot particle aggregate is obtained according to any of the above-mentioned preparation methods, and the above-mentioned quantum dot particle aggregate is subjected to a crushing treatment or not, melt-extruded and solidified into shape to obtain the above-mentioned photoconversion device.
[0016] According to the third aspect of the present application, a quantum dot particle is provided, comprising a core of a first polymer particle and a shell of a second polymer, wherein a plurality of first quantum dots are located in the shell of the second polymer, and the minimum size of the first polymer particle is greater than or equal to 0.3 mm.
[0017] Furthermore, the core of the first polymer particle and the shell of the second polymer particle are connected by non-chemical bonds.
[0018] Furthermore, the quantum dot particles further include a shell of a third polymer, and the shell of the third polymer is located outside the shell of the second polymer.
[0019] Furthermore, the quantum dot particles further include a shell of a third polymer, the shell of the third polymer is located outside the shell of the second polymer, and the plurality of second quantum dots are located in the shell of the third polymer.
[0020] Furthermore, the quantum dot particles further include a shell of a fourth polymer, and the shell of the fourth polymer is located outside the shell of the third polymer.
[0021] Furthermore, the fluorescence quantum efficiency of the quantum dot particles is greater than or equal to 90%, and the fluorescence half-peak width of the quantum dot particles is less than or equal to 25 nm.
[0022] Furthermore, the first polymer and the second polymer are the same or different. Preferably, the molecular weight of the first polymer is 30,000 to 600,000, and the molecular weight of the second polymer is 5,000 to 200,000.
[0023] Furthermore, the second polymer and the third polymer are the same or different, and preferably the molecular weight of the second polymer is smaller than the molecular weight of the third polymer.
[0024] Further, the material of the first polymer particles includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer and polyethylene terephthalate; the second polymer or the third polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer and polyethylene terephthalate; the fourth polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer and polyethylene terephthalate.
[0025] According to the fourth aspect of the present application, a quantum dot particle assembly is provided, the quantum dot particle assembly comprising a plurality of quantum dot particles as described above, the quantum dot particles being dispersed in a polymer matrix, the material of the polymer matrix being the same as the polymer of the outermost shell of the quantum dot particles.
[0026] Furthermore, the quantum dot particles and the polymer matrix are connected by non-chemical bonds. Preferably, the impact strength of the polymer matrix between the quantum dot particles is less than or equal to 2.1 kJ / m 2 .
[0027] In the embodiment of the method for preparing quantum dot particle assemblies, compared with the traditional quantum dot particle preparation process, the quantum dots are not mixed with blank polymer materials and subjected to high-temperature extrusion granulation, thereby avoiding damage to the quantum dots by the high-temperature process, and the life of the application product can be improved; the prepared quantum dot particle assembly can be directly used or can be used for the preparation of quantum dot photoconversion devices after a crushing process, making the preparation process of the quantum dot particle assembly simple and low-cost. In addition, the first polymer particles serve as carriers for quantum dot loading, and the larger-sized first polymer particles lay the foundation for the size of the quantum dot particles. The larger-sized quantum dot particles are conducive to the uniform mixing of the luminescent materials. In the preparation method of the photoconversion device, the uniformity of the melt co-extrusion product can be improved, which is conducive to improving the light uniformity of the photoconversion device. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0029] Figure 1 A schematic diagram of the appearance and a top view of the cross section of a single-shell quantum dot particle are shown;
[0030] Figure 2 A schematic diagram of the appearance of another double-shell quantum dot particle and a top view of the cross section are shown;
[0031] Figure 3 A schematic diagram showing a cross section of a quantum dot particle assembly;
[0032] Figure 4 A schematic diagram showing a cross section of a small aggregate of a quantum dot particle aggregate after being broken;
[0033] Figure 5 A photo of quantum dot particles obtained by a preparation method of an embodiment is shown;
[0034] Figure 6A photograph of quantum dot particles obtained by a comparative example preparation method is shown. DETAILED DESCRIPTION
[0035] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0036] It should be noted that the terms "first", "second", "A", "B" etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequential order. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described here. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, the process, method, system, product or equipment comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or equipment.
[0037] The following will describe in more detail the exemplary embodiments of the quantum dot particle assembly, the preparation method of the photoconversion device and the quantum dot particles provided by the present application. However, these exemplary embodiments can be implemented in a variety of different forms and should not be interpreted as being limited to the embodiments described herein. It should be understood that these embodiments are provided to make the disclosure of the present application thorough and complete, and to fully convey the concepts of these exemplary embodiments to ordinary technicians in the field.
[0038] As introduced in the background technology, the performance of quantum dot photoconversion devices in the prior art is relatively low, and a process is needed to maintain the original performance of quantum dots or reduce the degradation of the original performance of quantum dots. The inventor believes that the high temperature process in the granulation process of quantum dot particles in the prior art damages the quantum dots, so it is necessary to reduce the high temperature damage. Therefore, in the first aspect of the present application, a method for preparing a quantum dot particle assembly is provided, wherein a plurality of first polymer particles, a first quantum dot solution and a second polymer solution are mixed and dried to obtain an assembly containing a plurality of quantum dot particles A, wherein the quantum dot particle A includes a core of a first polymer particle, a shell of a second polymer formed by a second polymer, a plurality of first quantum dots are located in the shell of the second polymer, and the minimum size of the first polymer particle is greater than or equal to 0.3 mm.
[0039] Compared with the traditional quantum dot particle preparation process, quantum dots are not mixed with blank polymer materials for high-temperature extrusion granulation, thereby avoiding damage to quantum dots by high temperature. The quantum dot particle aggregate can be used directly or slightly crushed for the preparation of quantum dot photoconversion devices, which has a simple process and low cost. In addition, the larger first polymer particles lay the foundation for the size of quantum dot particles. The larger size of the quantum dot particle aggregate is conducive to the uniform mixing of the luminescent material (nano size), improving the uniformity of the melt co-extrusion product, and helping to improve the light uniformity of the final photoconversion device.
[0040] The above “minimum dimension” refers to the length of the shortest line segment of any cross section of the first polymer particle. The above “maximum dimension” refers to the length of the longest line segment of any cross section of the first polymer particle. The above “plurality” only modifies the first polymer particles.
[0041] In some embodiments, the first polymer particles may have micropores or may not have micropores, and the quantum dots may or may not enter the micropores.
[0042] In some embodiments, the minimum size of the first polymer particles is greater than or equal to 1 mm. In some embodiments, the minimum size of the first polymer particles is 0.3 to 10 mm, or 0.5 to 10 mm. In some embodiments, the minimum size of the first polymer particles is 1 to 20 mm, or 1 to 10 mm, or 1 to 8 mm. In some embodiments, the maximum size of the first polymer particles is 2 to 30 mm, or 2 to 20 mm, or 2 to 10 mm, or 5 to 10 mm. In some preferred embodiments, the average size (average of the maximum size and the minimum size) of the first polymer particles is 2 to 5 mm.
[0043] The schematic diagram of the structure of quantum dot particle A is shown in Figure 1 Whether the size of the quantum dot particles A obtained in the subsequent operation is uniform is related to the preparation process and can be adjusted to a relatively uniform size distribution state, such as Figure 5 Photos shown.
[0044] It should be noted that the quantum dot particle assembly refers to an assembly of multiple quantum dot particles. In one embodiment of the assembly of quantum dot particles A, multiple first polymer particles are dispersed in the second polymer, and the molecular chains of the second polymer cover each first polymer particle, such as Figure 3 As shown, at this time, there is no boundary between the quantum dot particles A (it is artificially believed that there are multiple quantum dot particles A, and additional operations such as crushing are required to obtain multiple quantum dot particles A). In other embodiments, the prepared quantum dot particle assembly can be composed of multiple parts, such as multiple small assemblies, or multiple small assemblies and multiple quantum dot particles A.
[0045] In some embodiments, the aggregate of quantum dot particles A can be subjected to a simple crushing process, such as natural crushing (without artificial force factors), to separate multiple quantum dot particles A and / or small aggregates containing multiple quantum dot particles A. The sizes of the various quantum dot particles A can be the same or different, and the shapes can be regular or irregular. The different or irregular shapes can reduce the difficulty of preparing quantum dot particles. The quantum dot particles A or small aggregates (containing a smaller number of first polymer particles than the original aggregate) can be directly melted in an extruder, without the need for additional steps to prepare a photoconversion device, thereby reducing production costs.
[0046] In some embodiments, the internal connection force of the second polymer is weak, and the aggregate naturally splits (without intentional pressure), forming multiple small quantum dot particle aggregates with smaller volumes, or multiple individual quantum dot particles. In layman's terms, the quantum dot aggregates "fall apart". These quantum dot particle aggregates or quantum dot particles of different volumes can be used as raw materials for preparing light conversion devices.
[0047] In some embodiments, the raw material of the first polymer particles does not include quantum dots. In some embodiments, the light transmittance of the first polymer particles is greater than or equal to 70%, or the light transmittance of the first polymer particles is greater than or equal to 80%. The light transmittance of the second polymer is greater than or equal to 70%, or the light transmittance of the second polymer is greater than or equal to 80%.
[0048] In a preferred embodiment, the solvent in the second polymer solution and the solvent in the first quantum dot solution are mutually soluble, so that the quantum dots are better dispersed in the second polymer. The boiling points of the solvents of both are less than or equal to 150° C., which facilitates low-temperature drying.
[0049] The above drying does not mean that the solvent is 100% volatilized, and some solvent may remain as long as it does not affect subsequent processing. The above drying can be carried out in multiple stages, such as preliminary drying first and then complete drying.
[0050] In some embodiments, the first quantum dot solution and the second polymer solution are both solutions containing both quantum dots and polymers.
[0051] In some embodiments, the solvent in the second polymer solution can dissolve the first polymer particles, so that the surface of the first polymer particles has a first polymer molecular chain, and the second polymer molecular chain in the second polymer solution is entangled with each other, so that the second polymer covers the first polymer particles more firmly. It should be noted that although the solvent in the second polymer solution can dissolve the first polymer particles, as long as the time and the type / amount of the solvent are well controlled, the first polymer particles can be partially dissolved without being completely dissolved. At the same time, the "core of the first polymer particle" in the above-mentioned "quantum dot particle A includes the core of the first polymer particle and the shell of the second polymer formed by the polymerization of the second polymer precursor" is a first polymer particle whose surface has been dissolved (or etched), which is slightly different from the first polymer particle of the raw material, and the shell is not purely the second polymer. However, it should be understood that this situation also falls within the scope of protection of the present application.
[0052] In other embodiments, the solvent in the second polymer solution cannot dissolve the first polymer particles, and the coating strength of the second polymer on the first polymer particles is not as strong as the aforementioned case where the two polymer molecular chains are entangled.
[0053] In some embodiments, the shell of the second polymer may completely cover the core of the first polymer particle, or may partially cover the first polymer particle, or both.
[0054] In some embodiments, an aggregate containing multiple quantum dot particles A is crushed to obtain multiple quantum dot particles A, and the multiple quantum dot particles A and a third polymer solution are mixed and dried to obtain an aggregate containing multiple quantum dot particles B, wherein the quantum dot particle B includes a core of a quantum dot particle A and a shell of a third polymer formed by a third polymer.
[0055] The above-mentioned crushing includes applying external force to cause the aggregate to split, and obtaining multiple quantum dot particles A, thereby preparing for the next step of coating the third polymer; since the second polymer is a ready-made polymer, not obtained by polymerization reaction during the preparation of the aggregate, the internal connection force of the second polymer molecular chain is not strong and is easy to split. Through the polymer shell coating, further protection of the quantum dots is achieved. It should be noted that the "crushing" mentioned in this application includes the crushing of non-artificially manipulated external forces, that is, it includes natural crushing and artificial crushing. In addition, although the application uses the expression "mixing and drying material 1 and material 2", the raw materials for preparing the aggregate can also include other materials, not limited to material 1 and material 2. For example, in some embodiments, after crushing the aggregate containing multiple quantum dot particles A, multiple quantum dot particles A and multiple small aggregates E of quantum dot particles A are obtained, and the multiple quantum dot particles A, the small aggregates E of multiple quantum dot particles A and the third polymer solution are mixed and dried to obtain an aggregate containing multiple quantum dot particles B, and the quantum dot particle B includes a core of a quantum dot particle A and a shell of a third polymer formed by a third polymer. At the same time, the quantum dot particle assembly also includes a plurality of small assemblies E of quantum dot particles A as cores and small assemblies F of the third polymer as shells.
[0056] In some embodiments, the shell of the third polymer has a thickness of 0.1 mm to 3 mm. In some embodiments, the shell of the third polymer may fully cover the core or partially cover the core.
[0057] In some embodiments, a plurality of quantum dot particles A are obtained by crushing an aggregate containing a plurality of quantum dot particles A, and the plurality of quantum dot particles A are mixed and dried with a second quantum dot solution and a third polymer solution to obtain an aggregate containing a plurality of quantum dot particles B', wherein the quantum dot particle B' comprises a core of a quantum dot particle A and a shell of a third polymer formed by a third polymer, and a plurality of second quantum dots are located in the shell of the third polymer. In some embodiments, the thickness of the shell of the third polymer is 0.1 mm to 3 mm.
[0058] In some embodiments, after the aggregate containing multiple quantum dot particles A is broken, multiple quantum dot particles A and multiple small aggregates E of quantum dot particles A are obtained. The multiple quantum dot particles A and the small aggregates E of multiple quantum dot particles A, the second quantum dot solution, and the third polymer solution are mixed and dried to obtain an aggregate containing multiple quantum dot particles B', wherein the quantum dot particle B' includes a core of a quantum dot particle A and a shell of a third polymer formed by a third polymer, and multiple second quantum dots are located in the shell of the third polymer. At the same time, the aggregate also includes a small aggregate F with multiple small aggregates E of quantum dot particles A as the core and the third polymer as the shell, and multiple second quantum dots are located in the shell of the third polymer.
[0059] In some embodiments, the light transmittance of the third polymer is greater than or equal to 70%, or the light transmittance of the third polymer is greater than or equal to 80%.
[0060] In some embodiments, after the aggregate containing multiple quantum dot particles B is crushed, multiple quantum dot particles B are obtained, and multiple quantum dot particles B, a second quantum dot solution, and a fourth polymer solution are mixed and dried to obtain an aggregate containing multiple quantum dot particles C, wherein the quantum dot particle C includes a core of a quantum dot particle B and a shell of a fourth polymer formed by a fourth polymer, and multiple second quantum dots are located in the shell of the fourth polymer. The shell of the fourth polymer further protects the quantum dots. In some embodiments, the thickness of the shell of the fourth polymer is 0.1 mm to 3 mm.
[0061] In some embodiments, the light transmittance of the fourth polymer is greater than or equal to 70%, or the light transmittance of the fourth polymer is greater than or equal to 80%.
[0062] In some embodiments, any of the above quantum dot particles and the polymer matrix (such as the second polymer, the third polymer, and the fourth polymer) are connected by non-chemical bonds, which facilitates breaking the aggregate and thus peeling off the quantum dot particles.
[0063] In some embodiments, the impact strength of the polymer matrix between any of the quantum dot particles is less than or equal to 2.1 kJ / m 2 .
[0064] In some embodiments, the first quantum dots in the first quantum dot solution and the second quantum dots in the second quantum dot solution may be completely identical, partially identical, or completely different, such as components, emission wavelengths, fluorescence half-peak widths, and processing techniques. The quantum dots in the first quantum dot solution are one or more, and the quantum dots in the second quantum dot solution are one or more.
[0065] In some embodiments, different types of quantum dots may have different matching polymers, so different quantum dots are matched with different polymers and processed into the same quantum dot particle assembly through a two-step coating method. If the quantum dots are of the same type, this method can also be used.
[0066] In some embodiments, the mixing is carried out by stirring. In some embodiments, the mixing is carried out to achieve a uniform mixing state as much as possible.
[0067] In some embodiments, the first quantum dots and the second quantum dots are not perovskite quantum dots, graphene quantum dots, carbon quantum dots, silicon quantum dots, or germanium quantum dots.
[0068] In some embodiments, the quantum dot particle assembly contains cadmium less than or equal to 100 ppm.
[0069] In some embodiments, the fourth polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and polyethylene terephthalate.
[0070] In some embodiments, the second quantum dot solution includes 0.1 wt % to 5 wt % of second quantum dots, and the second quantum dots are the same as or different from the first quantum dots.
[0071] In some embodiments, in the raw material, the mass ratio of the plurality of first polymer particles to the second polymer is 100:1 to 100:10, and the mass ratio of the first quantum dots to the second polymer is 0.1:100 to 5:100.
[0072] In some embodiments, the first quantum dot solution includes 0.1 wt % to 5 wt % of the first quantum dots.
[0073] In some embodiments, the first polymer particles are in the shape of a cylinder or a cuboid. Regular first polymer particles are easier to process and prepare.
[0074] In some embodiments, the material of the first polymer particles includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, and polyethylene terephthalate.
[0075] In some embodiments, the second polymer or the third polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and polyethylene terephthalate.
[0076] In some embodiments, the fluorescence quantum efficiency of the quantum dot particles (quantum dot particles A or B or B' or C) is greater than or equal to 90%, and the fluorescence half-peak width of the quantum dot particles (quantum dot particles A or B or B' or C) is less than or equal to 25 nm.
[0077] In some embodiments, the first polymer and the second polymer are the same or different. In some embodiments, the molecular weight of the first polymer is 30,000 to 600,000, and the molecular weight of the second polymer is 5,000 to 200,000.
[0078] In some embodiments, the second polymer and the third polymer are the same or different. In some embodiments, the molecular weight of the second polymer is less than the molecular weight of the third polymer. In some embodiments, the molecular weight of the second polymer is 5,000 to 200,000, and the molecular weight of the third polymer is 10,000 to 300,000.
[0079] The second aspect of the present application provides a method for preparing a photoconversion device, wherein a quantum dot particle assembly is obtained according to any of the above methods, and the quantum dot particle assembly is subjected to a crushing process or not, melt-extruded and solidified to obtain a photoconversion device. The method for preparing a photoconversion device avoids high-temperature damage during the preparation of quantum dot particles, reduces high-temperature damage to quantum dots during the entire photoconversion device preparation process, and can achieve uniform light output of the photoconversion device. If the assembly is not crushed, its size should meet the feed size requirements of the extruder feed port.
[0080] The parameters of the above melt extrusion and solidification can refer to the prior art.
[0081] The third aspect of the present application provides a quantum dot particle, comprising a core of a first polymer particle, a shell of a second polymer, a plurality of first quantum dots located in the shell of the second polymer, and a minimum size of the first polymer particle being greater than or equal to 0.3 mm. The quantum dot particle size is suitable for existing extrusion processes and equipment, facilitates uniform mixing of materials, has a low manufacturing cost, is conducive to uniform distribution of quantum dots in the final product, and thus improves the luminescence uniformity of the final product.
[0082] In some embodiments, the core of the first polymer particle does not include quantum dots. In some embodiments, the core of the first polymer particle is connected to the shell of the second polymer by a non-chemical bond.
[0083] In some embodiments, the minimum dimension of the first polymer particles is 0.3 to 10 mm. In some embodiments, the minimum dimension of the first polymer particles is 1 to 20 mm, or 1 to 10 mm, or 1 to 8 mm. In some embodiments, the maximum dimension of the first polymer particles is 2 to 30 mm, or 2 to 20 mm, or 2 to 10 mm. In some preferred embodiments, the average dimension (average of the maximum dimension and the minimum dimension) of the first polymer particles is 2 to 5 mm.
[0084] In some embodiments, the quantum dot particle further includes a shell of a third polymer, the shell of the third polymer being located outside the shell of the second polymer.
[0085] In some embodiments, the quantum dot particle further includes a shell of a third polymer, the shell of the third polymer is located outside the shell of the second polymer, and the quantum dot particle further includes a plurality of second quantum dots located in the shell of the third polymer.
[0086] In some embodiments, the quantum dot particle further comprises a shell of a fourth polymer, and the shell of the fourth polymer is located outside the shell of the third polymer. In other embodiments, the quantum dot particle further comprises shells of n polymers, where n is an integer greater than 4.
[0087] In some embodiments, the fluorescence quantum efficiency of the quantum dot particles is greater than or equal to 90%, and the fluorescence half-peak width of the quantum dot particles is less than or equal to 25 nm.
[0088] In some embodiments, the first polymer and the second polymer are the same or different. In some embodiments, the molecular weight of the first polymer is 30,000 to 600,000, and the molecular weight of the second polymer is 5,000 to 200,000.
[0089] In some embodiments, the second polymer and the third polymer are the same or different. In some embodiments, the molecular weight of the second polymer is less than the molecular weight of the third polymer.
[0090] In some embodiments, the molecular weight of the second polymer is 5,000 to 200,000, and the molecular weight of the third polymer is 10,000 to 300,000. According to the different molecular weights of the polymers, the internal connection strength of the molecular chains after the polymers are dissolved and reconnected after drying is different, and quantum dot particles of different particle sizes can be adjusted.
[0091] In some embodiments, the average size of the quantum dot particles is 1 mm to 8 mm.
[0092] In some embodiments, the material of the first polymer particles includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, and polyethylene terephthalate.
[0093] In some embodiments, the second polymer or the third polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and polyethylene terephthalate.
[0094] In some embodiments, the fourth polymer comprises one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and polyethylene terephthalate.
[0095] The fourth aspect of the present application provides a quantum dot particle assembly, which includes a plurality of quantum dot particles of any of the above-mentioned types, wherein the quantum dot particles are dispersed in a polymer matrix, and the material of the polymer matrix is the same as the polymer of the outermost shell of the quantum dot particles.
[0096] In some embodiments, the quantum dot particles and the polymer matrix are connected by non-chemical bonds, which facilitates the stripping of the quantum dot particles from the aggregate.
[0097] In some embodiments, the impact strength of the polymer matrix between the quantum dot particles is less than or equal to 2.1 kJ / m 2 . It is convenient to peel the quantum dot particles from the aggregate.
[0098] In some embodiments, the quantum dot particles differ in size, or in shape, or in both size and shape.
[0099] The preparation method of the quantum dot particle assembly and the preparation method of the photoconversion device of the present invention will be further described below with reference to the examples.
[0100] Example 1
[0101] First, the first polymer particles are selected as polymethyl methacrylate (PMMA for short), with a molecular weight of about 100,000 and an average particle size of about 3 mm. Take 1wt% quantum dot toluene solution, in which the mass ratio of red and green quantum dots is 1:1.2, and mix it with 50wt% PMMA polymer (Mw is about 10,000) toluene solution at a mass ratio of 1:10 to obtain the first quantum dot-PMMA toluene solution.
[0102] The second step is to mix the first polymer particles and the first quantum dot-PMMA toluene solution in a mass ratio of 100:1 and stir to mix, and at the same time, vacuum to remove the toluene solvent to obtain a quantum dot particle assembly in which some of the first polymer particles are connected via PMMA and the outer layer is coated with a quantum dot-PMMA polymer.
[0103] Finally, a drying and separation operation is performed: the quantum dot particle aggregate is vacuum dried at 80°C for 3 hours to further remove the remaining solvent, and the dried material is crushed and separated in a mixer with a rotation speed set at 100RPM to separate part of the aggregate into single particles. The resulting particles are the final quantum dot particles A, in which the quantum dots are distributed in the shell layer with a shell layer thickness distribution of 0.01 to 0.1 mm and a quantum dot mass fraction of approximately 0.2wt%.
[0104] The quantum dot-PMMA polymer aggregate was made into a notched cantilever beam impact tester standard specimen according to the standard ISO 180 method, and the specimen impact strength was tested according to the standard test method. The test value was 0.8 kJ / m 2.
[0105] Example 2
[0106] The quantum dot particles A obtained in Example 1 were stirred and mixed with 50wt% of PMMA oligomer (Mw of about 20,000) toluene solution at a mass ratio of 100:1, and the toluene solvent was removed by vacuum. The same drying and separation operation as in Example 1 was performed to obtain quantum dot particles B having a first polymer particle as a core, a PMMA first shell layer of quantum dots (concentration of about 0.2wt%), and a PMMA second shell layer without quantum dots.
[0107] Example 3
[0108] The difference from Example 2 is that first, 0.1wt% quantum dot toluene solution and 50wt% PMMA oligomer (Mw about 20,000) toluene solution are mixed in a mass ratio of 1:10, wherein the mass ratio of red and green quantum dots is 1:1.2, to obtain a second quantum dot-PMMA toluene solution.
[0109] The quantum dot particles A and the second quantum dot-PMMA toluene solution were mixed in a mass ratio of 100:1, stirred evenly, and the toluene solvent was removed by vacuum to obtain a quantum dot particle assembly in which the quantum dot particles A were connected via PMMA and the outer layer was coated with quantum dot-PMMA oligomers.
[0110] Finally, the same drying and separation operation as in Example 1 was used to obtain a plurality of quantum dot particles B' with the first polymer particles as the core, quantum dots (concentration of 0.2 wt%) PMMA as the first shell layer, and quantum dots (concentration of 0.02 wt%) PMMA as the second shell layer.
[0111] Example 4
[0112] The difference from Example 2 is that first, 0.1wt% quantum dot toluene solution and 50wt% polystyrene (PS) oligomer (Mw about 20,000) toluene solution are mixed in a mass ratio of 1:10, wherein the mass ratio of red and green quantum dots is 1:1.2, to obtain a third quantum dot-PS toluene solution.
[0113] The quantum dot particles A and the third quantum dot-PS toluene solution were mixed in a mass ratio of 100:1, stirred evenly, and the toluene solvent was removed by vacuum to obtain quantum dot particles in which the quantum dot particles A were connected via PS and the outer layer was coated with quantum dot-PS oligomers.
[0114] Finally, the same drying and separation operation as in Example 1 was performed to obtain a plurality of quantum dot particles C with the first polymer particles as the core, a PMMA first shell layer with a quantum dot mass fraction of about 0.2 wt%, and a PS second shell layer with quantum dots (concentration 0.02 wt%).
[0115] Example 5
[0116] First, the first polymer particles are PMMA, with a molecular weight Mw of about 100,000 and an average particle size of about 3 mm.
[0117] Take 0.5 wt % of the green quantum dot toluene solution and mix it evenly with 50 wt % of the PMMA polymer (Mw is about 10,000) toluene solution at a mass ratio of 1:10 to obtain a fourth quantum dot-PMMA toluene solution.
[0118] A 0.5 wt % red quantum dot toluene solution was taken and mixed evenly with a 50 wt % PMMA polymer (Mw of about 10,000) toluene solution at a mass ratio of 1:10 to obtain a fifth quantum dot-PMMA toluene solution.
[0119] In the first step, the first polymer particles and the fourth quantum dot-PMMA toluene solution are mixed in a mass ratio of 100:1 and stirred, and the toluene solvent is removed by vacuum to obtain a quantum dot aggregate 1 in which the first polymer particles are connected via PMMA and the outer layer is coated with a quantum dot-PMMA polymer.
[0120] Drying and separation operation is performed: the quantum dot particle aggregate 1 is vacuum dried at 80°C for 3 hours to further remove the remaining solvent, and the dried material is crushed and separated in a mixer, and the rotation speed is set to 100RPM to separate part of the quantum dot particle aggregate into single particles. The obtained quantum dot particle material is the quantum dot particle containing a green quantum dot shell, wherein the green quantum dots are distributed in the shell, the shell thickness distribution is 0.01 to 0.1 mm, and the quantum dot mass fraction is about 0.1wt%.
[0121] In the second step, the quantum dot particles and the fifth quantum dot-PMMA toluene solution are mixed in a mass ratio of 100:1 and stirred, and the toluene solvent is removed by vacuum to obtain a quantum dot particle assembly 2 in which some quantum dot particles are connected via PMMA and the outer layer is coated with a quantum dot-PMMA polymer.
[0122] Finally, a drying and separation operation is performed: the quantum dot particle assembly 2 is vacuum dried at 80°C for 3 hours to remove the remaining solvent, and the dried material is crushed and separated in a mixer. The rotation speed is set to 100RPM, so that part of the quantum dot particle assembly 2 is separated into single granules. The obtained granules are quantum dot particles E', in which red quantum dots are distributed in the second shell layer, the shell layer thickness distribution is 0.01~0.1mm, and the quantum dot mass fraction is about 0.1wt%; the green quantum dots are distributed in the first shell layer, the shell layer thickness distribution is 0.01~0.1mm, and the quantum dot mass fraction is about 0.1wt%.
[0123] Comparative Example 1
[0124] Through the traditional granulation process, a 1wt% quantum dot toluene solution was used, wherein the mass ratio of red and green quantum dots was 1:1.2, and the ratio of quantum dot solution to white PMMA (molecular weight of 100,000) was 1:1000, and twin-screw extrusion granulation was performed, wherein the temperature was set to 230°C, and the average pellet size was about 3mm. The obtained quantum dot polymer particles are shown in Figure 6 , quantum dots are dispersed more evenly in the PMMA matrix.
[0125] Comparative Example 2
[0126] Take 1wt% quantum dot toluene solution, in which the mass ratio of red and green quantum dots is 1:1.2, mix the first polymer particles and the first quantum dot toluene solution in a mass ratio of 1000:1, stir and mix, and vacuum to remove the toluene solvent to obtain polymer particles with quantum dots wrapped in the outer layer of the first polymer particles.
[0127] The red quantum dots used in the above-mentioned embodiments and comparative examples are consistent, and the green quantum dots are also consistent, so as to facilitate comparison of the results.
[0128] Preparation of quantum dot diffuser plate:
[0129] 5% by mass of diffusion particles (titanium dioxide and silicon oxide) were mixed with polymethyl methacrylate matrix white material, and extruded and granulated at 230°C by an extrusion granulator to obtain the first diffusion masterbatch, which was used as the raw material for the first diffusion layer; 10% by mass of diffusion particles (titanium dioxide and silicon oxide) were mixed with matrix white material, and extruded and granulated at 230°C by an extrusion granulator to obtain the second diffusion masterbatch, which was used as the raw material for the second diffusion layer. The first diffusion masterbatch was mixed with polymethyl methacrylate matrix white material (mass ratio 10:100, and the ratios in brackets below are all mass ratios unless otherwise specified) and added to the first secondary extruder, the second diffusion masterbatch was mixed with polymethyl methacrylate matrix white material (10:100) and added to the second secondary extruder, and the quantum dot particle assembly (from Examples 1 to 3, Example 5, and Comparative Example 1) was added to the main extruder, and the thickness of each layer was controlled to be 1:4:1, and extruded at 230°C by a three-layer co-extrusion process, and the quantum dot diffusion plate was obtained by roller (smooth roller) cooling and cutting.
[0130] 5% by mass of diffusion particles (titanium dioxide and silicon oxide) were mixed with PS matrix white material, and extruded and granulated at 230°C by an extrusion granulator to obtain the first diffusion masterbatch, which was used as the raw material for the first diffusion layer; 10% by mass of diffusion particles (titanium dioxide and silicon oxide) were mixed with matrix white material, and extruded and granulated at 230°C by an extrusion granulator to obtain the second diffusion masterbatch, which was used as the raw material for the second diffusion layer. The first diffusion masterbatch was mixed with PS matrix white material (mass ratio 10:100, and the ratios in brackets below are all mass ratios unless otherwise specified) and added to the first secondary extruder, the second diffusion masterbatch was mixed with PS matrix white material (10:100) and added to the second secondary extruder, and the quantum dot particle assembly (from Example 4) was added to the main extruder, and the thickness of each layer was controlled and adjusted to 1:4:1, and extruded at 230°C by a three-layer co-extrusion process, and the quantum dot diffusion plate was obtained by roller (a smooth roller) cooling and cutting.
[0131] The performance of the quantum dot diffusion plate prepared above was tested. The method for detecting the luminous efficiency of the quantum dot diffusion plate is: using a 450nm blue LED lamp as a backlight source, the first diffusion layer is far away from the LED light source, and the second diffusion layer is close to the LED light source. The blue backlight spectrum and the spectrum through the quantum dot diffusion plate are tested using an integrating sphere, and the quantum dot luminous efficiency is calculated using the integral area of the spectrum.
[0132] Fluorescence quantum efficiency of the diffuser = quantum dot emission peak area / (blue backlight peak area-blue peak area that is not absorbed by the quantum dot diffuser)*100%.
[0133] The luminous stability test method of the diffuser plate is: The luminous stability test method mainly includes high temperature blue light illumination (70℃, blue light wavelength 450nm, average light intensity 0.5W / cm 2 ), high temperature and humidity (65°C / 95% relative humidity) and high temperature storage (85°C) and other aging conditions, the fluorescence quantum efficiency of the quantum dot diffusion plate was detected. The initial efficiency of each embodiment and comparative example was set to 100%.
[0134] Table 1:
[0135]
[0136] It can be seen from Table 1 that the accelerated aging test results of each embodiment are better than those of the comparative example, and the life of the photoconversion device is significantly improved, which indirectly proves that the process can avoid or reduce high-temperature damage to quantum dots.
[0137] The quantum dot diffusion plates of the same size prepared from the materials of Examples 1 to 5 and Comparative Example 1 were placed in the same backlight module, and the chromaticity uniformity and brightness of the backlight module were tested and recorded in Table 2. CIE (x, y) is the chromaticity coordinate value, and 3×3 points with equal spacing are selected. The CIE-x deviation value = the maximum value of CIE-x minus the minimum value of CIE-x, and the CIE-y deviation value = the maximum value of CIE-y minus the minimum value of CIE-y. The smaller the CIE-x deviation value and the CIE-y deviation value, the better the chromaticity uniformity of the backlight unit. Brightness uniformity = minimum brightness value among 9 points / maximum brightness value among 9 points, and the closer the brightness uniformity is to 1, the more uniform the brightness is, the CIE-x chromaticity uniformity improvement percentage = (CIE-x deviation value of comparison example 1 - CIE-x deviation value of this embodiment) / CIE-x deviation value of comparison example 1, CIE-y chromaticity uniformity improvement percentage = (CIE-y deviation value of comparison example 1 - CIE-y deviation value of this embodiment) / CIE-y deviation value of comparison example 1.
[0138] Table 2:
[0139]
[0140] It can be seen from Table 2 that the brightness uniformity of each embodiment is improved, and the chromaticity uniformity is greatly improved.
[0141] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a quantum dot particle assembly, characterized in that: A plurality of first polymer particles, a first quantum dot solution and a second polymer solution are mixed and dried to obtain an aggregate containing a plurality of quantum dot particles A, wherein the quantum dot particles A include a core of a first polymer particle and a second polymer shell formed by a second polymer, and a plurality of the first quantum dots are dispersed in the shell of the second polymer, and the minimum size of the first polymer particles is greater than or equal to 0.3 mm.
2. The method for preparing a quantum dot particle assembly according to claim 1, characterized in that: The aggregate containing multiple quantum dot particles A is crushed to obtain multiple quantum dot particles A, and the multiple quantum dot particles A and a third polymer solution are mixed and dried to obtain an aggregate containing multiple quantum dot particles B, wherein the quantum dot particle B includes a core of the quantum dot particle A and a shell of a third polymer formed by the third polymer.
3. The method for preparing a quantum dot particle assembly according to claim 1, characterized in that: The aggregate containing multiple quantum dot particles A is crushed to obtain multiple quantum dot particles A, and the multiple quantum dot particles A, the second quantum dot solution and the third polymer solution are mixed and dried to obtain an aggregate containing multiple quantum dot particles B', wherein the quantum dot particle B' includes a core of the quantum dot particle A and a shell of a third polymer formed by the third polymer, and multiple second quantum dots are located in the shell of the third polymer.
4. The method for preparing a quantum dot particle assembly according to claim 2, characterized in that: The aggregate containing multiple quantum dot particles B is crushed to obtain multiple quantum dot particles B, and the multiple quantum dot particles B, the second quantum dot solution and the fourth polymer solution are mixed and dried to obtain an aggregate containing multiple quantum dot particles C, wherein the quantum dot particle C includes a core of the quantum dot particle B and a shell of a fourth polymer formed by the fourth polymer, and multiple second quantum dots are located in the shell of the fourth polymer.
5. The method for preparing a quantum dot particle assembly according to claim 4, characterized in that: The fourth polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer and polyethylene terephthalate.
6. The method for preparing a quantum dot particle assembly according to claim 3 or 4, characterized in that: The second quantum dot solution includes 0.1 wt % to 5 wt % of the second quantum dots, and the second quantum dots are the same as or different from the first quantum dots.
7. The method for preparing a quantum dot particle assembly according to claim 1, characterized in that: The mass ratio of the plurality of first polymer particles to the second polymer is 100:1 to 100:10, and the mass ratio of the first quantum dots to the second polymer is 0.1:100 to 5:
100.
8. The method for preparing a quantum dot particle assembly according to claim 1, characterized in that: The first quantum dot solution includes 0.1 wt % to 5 wt % of the first quantum dots.
9. The method for preparing a quantum dot particle assembly according to claim 1, characterized in that: The first polymer particles are in the shape of a cylinder or a cuboid.
10. The method for preparing a quantum dot particle assembly according to claim 1, characterized in that: The material of the first polymer particles includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer and polyethylene terephthalate.
11. The method for preparing a quantum dot particle assembly according to claim 2, characterized in that: The second polymer or the third polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer and polyethylene terephthalate.
12. A method for preparing a photoconversion device, characterized in that: The quantum dot particle aggregate is obtained according to any one of the preparation methods of claims 1 to 11, and the quantum dot particle aggregate is crushed or not crushed, melt-extruded and solidified to obtain the photoconversion device.
13. A quantum dot particle, characterized in that: The invention comprises a core of a first polymer particle and a shell of a second polymer, wherein a plurality of first quantum dots are dispersed in the shell of the second polymer, and a minimum size of the first polymer particle is greater than or equal to 0.3 mm.
14. The quantum dot particle according to claim 13, characterized in that: The core of the first polymer particle is connected to the shell of the second polymer particle by non-chemical bonds.
15. The quantum dot particle according to claim 13, characterized in that: The quantum dot particle further includes a shell of a third polymer, and the shell of the third polymer is located outside the shell of the second polymer.
16. The quantum dot particle according to claim 13, characterized in that: The quantum dot particle further includes a shell of a third polymer, the shell of the third polymer is located outside the shell of the second polymer, and a plurality of second quantum dots are located in the shell of the third polymer.
17. The quantum dot particles according to claim 15 or 16, characterized in that: The quantum dot particle further includes a shell of a fourth polymer, and the shell of the fourth polymer is located outside the shell of the third polymer.
18. The quantum dot particle according to claim 13, characterized in that: The fluorescence quantum efficiency of the quantum dot particles is greater than or equal to 90%, and the fluorescence half-peak width of the quantum dot particles is less than or equal to 25 nm.
19. The quantum dot particle according to claim 13, characterized in that: The first polymer and the second polymer are the same or different.
20. The quantum dot particle according to claim 13, characterized in that: The molecular weight of the first polymer is 30,000 to 600,000, and the molecular weight of the second polymer is 5,000 to 200,000.
21. The quantum dot particle according to claim 15 or 16, characterized in that: The second polymer and the third polymer are the same or different.
22. The quantum dot particle according to claim 15 or 16, characterized in that: The molecular weight of the second polymer is smaller than the molecular weight of the third polymer.
23. The quantum dot particle according to claim 17, characterized in that: The material of the first polymer particles includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer and polyethylene terephthalate; the second polymer or the third polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer and polyethylene terephthalate; the fourth polymer includes one or more of polystyrene, polymethyl methacrylate, polypropylene, polyethylene, acrylonitrile-styrene copolymer, polycarbonate, methyl methacrylate and styrene copolymer, polyvinyl alcohol, ethylene-vinyl alcohol copolymer and polyethylene terephthalate.
24. A quantum dot particle assembly, characterized in that: The quantum dot particle assembly comprises a plurality of quantum dot particles as claimed in any one of claims 13 to 23, wherein the quantum dot particles are dispersed in a polymer matrix, and the material of the polymer matrix is the same as the polymer of the outermost shell of the quantum dot particles.
25. The quantum dot particle assembly according to claim 24, characterized in that: The quantum dot particles and the polymer matrix are connected by non-chemical bonds.
26. The quantum dot particle assembly according to claim 25, characterized in that: The impact strength of the polymer matrix between the quantum dot particles is less than or equal to 2.1 kJ / m 2 .
Citation Information
Patent Citations
Quantum dot containing composite particle and method for fabricating the same
KR1020150123189A